ANGOLA'S REGIONAL FOREIGN POLICY: CHANGES FACING THE SYSTEMIC ORDER (1975-2010) - da Silva, Igor Castellano (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The article addresses Angola’s foreign policy towards Southern Africa (1975–2010) and assesses its posture facing the changing order of the regional system and explanations for such behavior, linked to the process of construction of the State and the interests and security of the elites that define foreign policy.